A compact reconfigurable sub-nanosecond pulse generator with pulse-shape modulation. Issue 4 (15th August 2016) - Valizade, Arash; Rezaei, Pejman; Orouji, Ali Asghar
Abstract : A new design of reconfigurable sub-nanosecond pulse generator (PG) with pulse shape selection ability is presented in this paper. Step recovery diode is used as the pulse sharpening device and the pulse shaping circuit consists of a controllable RC differentiator in which a single PIN diode is embedded, which provides two different switchable pulse shaping performances. The realized PG has a compact (10 × 12 mm 2 ) simple structure and is easy to implement while generating Gaussian and monocycle pulses with 510 and 660 ps pulse width, respectively. The proposed pulse shaping method is versatile and can be effectively modified and reconfigured to generate more complicated pulse shapes such as polycycle signals. The measured results reveal that the proposed reconfigurable PG is suitable to be used in systems with pulse shape modulation that require sub-nanosecond pulses at low pulse repetition rates.